Pengembangan LKS Biologi Berbasis Inkuiri Terbimbing Materi Sistem Regulasi - Sri Nengsih; Winda Afriani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study is to produce valid and practical guided inquiry based Biology LKS. This type of research is research and development. In this study, researchers used the development method using a 4-D model (four D), defining, designing, developing and disseminating. Guided Biological LKS based on valid inquiry, then tested in a limited way in MAN 3 Payakumbuh for students of class XI MIA. To see the practicality of Biology LKS, researchers used a questionnaire response sheet given to teachers and students. , resulting in an average percentage of 81.98% which belongs to a very valid category. The results of processing data from the practicality questionnaire the teacher's response obtained an average yield of 88.2% with a very practical category and the practicality of the student's response to an average of 81.9% with a very practical category. Conclusion, the development of guided inquiry-based Biology LKS material is a very practical regulatory system used for the learning process. Keywords: guided inquiry, LKS, regulation system